Evaluation of the history of caries and associated factors among quilombolas in Southeastern Brazil - Maria Cristina Almeida de Souza; Flávia Martão Flório (Universidade Estadual de Campinas, 2010)
Aim: To evaluate caries prevalence and associated factors in Quilombola communities. Methods: The study involved a cross-sectional study with Quilombola communities in Southeastern Brazil, in 2011. The data were collected by interviews and clinical examination. The sample was checked for caries prevalence (dmft and DMFT index) by one trained and calibrated dentist, reaching acceptable levels of agreement for data collection. The data were analyzed using descriptive statistics and frequency distribution. The significance of the associations between the dependent variable (dental caries) and the independent variables was verified using chi-squared or Fisher's Exact tests. Variables with a p-value <0.25 were tested using multiple logistic regression models in order to keep those with a pd"0.05 value. Odds ratios were estimated using regression models and 95% confidence intervals. The population consisted of 171 quilombolas (97% of total). Results: Mean dmft value was 1.91 (± 2.71) at age d"5 years and mean DMFT values were 1.20 (± 1.49), 3.50 (± 2.23), 10.3 (± 4.79), 22.9 (± 5.37), 22.8 (± 4.12), respectively in the age groups: 6-12, 13-18, 19-34, 35-59 years and 60 years or older. Age less than 5 years (p-value 0.014), own perception of oral health (p-value 0.040) and education level were variables associated with dental caries in permanent teeth and need for treatment in the deciduous dentition. Conclusions: High prevalence of dental caries indicates the need for restructuring the dental care provided to the quilombolas.